(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1869)
A special meeting was held to allow Professor George Stephens of Copenhagen to present a lecture while he was visiting Edinburgh. Professor Stephens spoke about the Runic inscriptions found on known monuments in Great Britain. He also suggested that the Society might encourage the preservation of the Ruthwell Cross, which was then debated by fellows. Meeting notes for 14 January, 1867 are appended.